Electronic engineering - Alley, Charles L. (John Wiley & Sons, 1962)
Contents: Electron Ballistics; Semiconductors; Diodes; Basic Amplifiers; The Common Emitter Amplifiers; Multielectrode Tubes and Transistors; Small Signal Amplifiers; Amplifiers with Extended Frequency Range; Small Signal Tuned Amplifiers; Large Signal Amplifiers; Amplifiers with Negative Feedback; Large Signal Tuned Amplifiers; Oscilator Circuits; Amplitude Modulation and Detection; Frequency Modulation; Nonlinear Analysis; Power Supplies.